Investigating Code Switching Used by English Teachers at SMPN 3 Pitumpanua - Tsamratul’aeni Tsamratul’aeni (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
In conducting this research, the researcher used total sampling technique by applying it with mixed method. The findings of this research based on problem statement indicated: 1) Factors triggering the use of Code switching by English teachers are rethoric reason, differences of status and formalities; lack of vocabulary. And another factors gather from the condition of the classroom, such as the students’ ability are not same; Code switching emerges spontaneously; help the students to participate more. 2) The English teachers used Code switching in the classroom almost all of the phase of learning process from beginning until the end. 3) Frequency and percentage of using code switching in the classroom by each English teacher was different. The highest frequency by teacher 1 (Frequency 80 times and percentage 32%); then teacher 2 (Frequency 24 times and percentage 19%); and the lowest frequency done by teacher 3 (Frequency 21 times & percentage 18%).